Spectrophotometric Evaluation of Antiepileptic Activity of Ficusracemosa in Chemicals Induced Epilepsy in Mice - Chavan, Prajakta J.; Vithal J Chawre, Atish B. Velhal.; Redasani, Vivek K. (Asian Journal of Pharmaceutical Research and Development, 2021)
Objective: To Evaluvate of Antiepileptic Acivity of Ficus Racemosa Extract Against Chemicals Induced epilepsy in mice, ficusracemosa is also used as antihyperglycemic, antiinflammatery , hepatoprotective action. Method : Anticonvulsant activity of three distinct dose levels of ethanolic extract of Ficus racemosa (100, 200, and 400 mg/kg) was tested in Swiss albino mice in seizures induced by Pentylenetetrazol (PTZ). Statistical analysis was carried out by one-way analysis of variance followed by Dunnett's test. Results: The presence of , flavonoids, were detected in the bark of Ficus racemosa. The extract dose-dependent effect in the delay of the onset of seizures and reduction in the duration of seizure.Conclusion : The ethanolic extract of Ficus racemosa exhibited significant and dose-dependent antiepileptic activity, which may be due to the presence of antioxidant principles like flavanoidsand other phytoconstituent produce protective activity againstPTZ.